Analysis of Shield Design Aspects of a Semi-Industrial Co-60 Gamma Irradiation Facility at Institute of Radiation and Polymer Technology of Bangladesh Atomic Energy Commission (Bangladesh Journal of Medical Physics, 2025)
The aim of this work is to evaluate the existing shield design aspects of a semi-industrial Cobalt-60 Gamma Irradiation Facility for 500 kCi, designed for irradiation of pharmaceutical products, daily food products, and pet/animal foods as well as research and development purposes at the Institute of Radiation and Polymer Technology (IRPT) of the Bangladesh Atomic Energy Commission. Earlier, the initial activity of this facility was 350 kCi and stone based reinforced concrete (SBRC) with a density 2.60 g/cc for specified thicknesses was used to shield the facility for safety to operational personnel and outside public. Due to increasing demand for irradiation services, the IRPT authority decided to raise the activity 500 kCi. For this reason, the shielding design aspects of this facility were needed to be recalculated and checked for safety. This analysis was done using the Point-kernel Shielding Code Micro-Shield 5.05 and public domain Point-kernel Shielding code QAD-CGGP2 respectively considering the radiation worker dose limit 10 μSv/hr and the public dose limit of 0.5 μSv/hr, as recommended by ICRP-60 (1990). The calculated dose rates at different locations around the facility are far below 10 μSv/hr except at positions D1, D4 and D7 inside the source room. No one is allowed to enter the source room when the facility is in ON mode. Therefore, this analysis reveals that the existing shield design aspects of IRPT’s Co-60 gamma source room is safe for 500 kCi and ensures radiation safety for both operating personnel and the public.Ban. J. Med. Phys., Vol -16, Issue -1, 2025 : 20-23